(untitled) (Journal of Global Arts Studies, 2025)
Background: Post 1990s Asia-Pacific biennials have evolved into geopolitical tools, mediating national image construction, visual sovereignty, and cultural capital through divergent curatorial and institutional strategies. Objective: To investigate how biennials serve as visual governance mechanisms within national soft power agendas, shaping identity narratives and mediating postcolonial-modern tensions. Methods: A triangulated approach combining historical-comparative case studies, critical curatorial discourse analysis, and socio-philosophical frameworks to decode biennials’ ideological, aesthetic, and political operations. Results: Asia-Pacific biennials function asymmetrically, mediating between artistic innovation and state interests. The four biennials all illustrate the dialectic of cultural emancipation and ideological containment. Conclusion: Asia-Pacific biennials expose the paradox of cultural diplomacy, functioning as hegemonic instruments that reproduce national ideologies under cosmopolitan veneers, necessitating deeper inquiry into their evolving techno-political roles.